Cytotoxicity and Apoptotic Effect of Nisin as an Effective Bacteriocin on the Cancer Cells - Samira Karimaei; Leonardo Oliveira Reis (Translational Research in Urology, 2020)
Different therapeutic approaches, comprising surgery, radiotherapy, chemotherapy are used for cancer treatment. There is an extreme need for novel anti-cancer agents with minimal toxicity for normal cells that are significantly growing. Nowadays, bacteriocins or antimicrobial peptides (AMPs) are considered tumor cell killers. In this regard, Nisin is one of the natural AMPs produced by Lactococcus lactis. Considering that Nisin could make apoptosis through inherent pathways and cause cancer cell death, it was suggested that at appropriate doses it might be efficient and safe for cancer treatment, room for future studies.